PEMBELAJARAN BINA DIRI DALAM MEMBANTU PEMAHAMAN KESEHATAN REPRODUKSI PADA REMAJA PUTRI TUNAGRAHITA - Tjasmini, Mimin (EDUTECH, 2014)
Abstract. mentally disabled adolescents besides experiencing barriers to the aspect of intelligence, they also have a drag on the aspect of social adaptation. They are less favored by other adolescents because of their behaviors that do not comply with the norms of society such as masturbating in any place, kissing anyone without shame, even having sexual intercourse, which in turn lead to pregnancy. Other conditions that make people in general dislike them because they look slouchy at the time of menstruation. Mentally disabled girls often do not realize if their shirt had been red by blood because her underwear is wet. The learning that leads to solving the above problem is the lesson of Self-Development. Self-Development means training skills for mentally disabled children to enable them to take care for themselves such as dressing, bathing, to the toilet (urinating, defecating) and to skillfully perform Vulva Hygiene. The obstacles faced in the Self-Development learning is in the lack of facilities and equipment to train the activity and the ability of teachers to find strategies, media and task analysis of the issues.Keywords: mentally disabled, female adolescents, Self-DevelopmentAbstrak, remaja tunagrahita selain mengalami hambatan pada aspek kecerdasan, mereka pun memiliki hambatan pada aspek adaptasi sosial. Mereka kurang disukai oleh remaja seusianya berkaitan dengan perilaku yang tidak sesuai dengan norma masyarakat seperti melakukan masturbasi disembarang tempat, tanpa rasa malu mencium siapa saja, bahkan melakukan hubungan seksual yang pada akhirnya menyebabkan kehamilan. Kondisi lain yang membuat orang pada umumnya kurang menyukai karena mereka berpenampilan jorok pada saat mengalami menstruasi. Anak tunagrahita tidak menyadari bajunya sudah merah oleh darah karena pakaian dalamnya sudah basah. Pembelajaran yang mengarah pada pemecahan masalah diatas yaitu pelajaran Bina Diri. Bina Diri berarti melatih keterampilan anak tunagrahita untuk mampu merawat diri seperti berpakaian, mandi, ke toilet (BAK, BAB) dan terampil melakukan Vulva Hygiene. Kendala – kendala yang dihadapi dalam pembelajaran Bina Diri berupa sarana dan alat untuk melatih kegiatan itu serta kemampuan guru dalam mencari strategi, media dan analisis tugas dari berbagai persoalan itu.Kata kunci : Anak Tunagrahita, Bina Diri.